Discontinuation of cost sharing in Uganda - Burnham Gilbert M.; Pariyo George; Galiwango Edward; Wabwire-Mangen Fred (The World Health Organization, 2004)
OBJECTIVE: To assess the effects of ending cost sharing on use of outpatient services and how this was perceived by health workers and members of a health unit management committee. METHODS: From 10 districts across Uganda, 78 health facilities were selected. Attendance at these facilities was assessed for eight months before and 12 months after cost sharing ended. The data represented 1 966 522 outpatient visits. Perceptions about the impact of ending cost sharing were obtained from the 73 health workers and 78 members of the health unit management committee who were available. FINDINGS: With the end of cost sharing, the mean monthly number of new visits increased by 17 928 (53.3%), but among children aged <5 years the increase was 3611 (27.3%). Mean monthly reattendances increased by 2838 (81.3%) among children aged <5 years and 1889 (24.3%) among all people. Attendances for immunizations, antenatal clinics, and family planning all increased, despite these services having always been free. Health workers reported a decline in morale, and many health unit management committees no longer met regularly. CONCLUSION: Use of all services increased - even those that had never before been subject to fees. The loss of some autonomy by the health facility and diminished community governance of health facilities may have long term negative effects.